(untitled) (Journal on Geoinformatics, Nepal, 2007)
In Nepal, the value and price of land in urban areas is very high. Due to the scale constraint, the cadastral maps prepared by graphical cadastral surveying method does not satisfy the land owners as they are asking for the accuracy of centimeter of land in the front face of their land parcel. The land owners are also asking for the recording and documentation of 3D real estate objects. Considering these facts, Cadastral Survey Branch under Survey Department has initiated digital cadastre program focusing on the urban land areas. Last year, the piloting of this program has been successfully completed to prepare digital cadastral database in ward number six of Banepa Municipality, Nepal. After the success of digital cadastral mapping, the programme has been continued and some observations are made. Some lessons have been learned from this programme for the cadastral information system (CIS) development in Nepal. There are various ways to evaluate the cadastral projects. In this paper an attempt has been done to evaluate the digital cadastre programme from Cadastre 2014 perspectives.